Analysis of Oxcarbazepine and the 10‐Hydroxycarbazepine Enantiomers in Plasma by LC‐MS/MS: Application in a Pharmacokinetic Study. Issue 12 (30th September 2013) - de, Natalicia; Wichert‐Ana, Lauro; Coelho, Eduardo Barbosa; Della Pasqua, Oscar; Alexandre, Veriano; Takayanagui, Osvaldo Massaiti; Tozatto, Eduardo; Lanchote, Vera Lucia
ABSTRACT Oxcarbazepine is a second‐generation antiepileptic drug indicated as monotherapy or adjunctive therapy in the treatment of partial seizures or generalized tonic–clonic seizures in adults and children. It undergoes rapid presystemic reduction with formation of the active metabolite 10‐hydroxycarbazepine (MHD), which has a chiral center at position 10, with the enantiomers (S)‐(+)‐ and R‐(−)‐MHD showing similar antiepileptic effects. This study presents the development and validation of a method of sequential analysis of oxcarbazepine and MHD enantiomers in plasma using liquid chromatography with tandem mass spectrometry (LC‐MS/MS). Aliquots of 100 μL of plasma were extracted with a mixture of methyl tert‐butyl ether: dichloromethane (2:1). The separation of oxcarbazepine and the MHD enantiomers was obtained on a chiral phase Chiralcel OD‐H column, using a mixture of hexane:ethanol:isopropanol (80:15:5, v/v/v) as mobile phase at a flow rate of 1.3 mL/min with a split ratio of 1:5, and quantification was performed by LC‐MS/MS. The limit of quantification was 12.5 ng oxcarbazepine and 31.25 ng of each MHD enantiomer/mL of plasma. The method was applied in the study of kinetic disposition of oxcarbazepine and the MHD enantiomers in the steady state after oral administration of 300 mg/12 h oxcarbazepine in a healthy volunteer. The maximum plasma concentration of oxcarbazepine was 1.2 µg/mL at 0.75 h. The kinetic disposition of MHD is enantioselective, with a higher proportion of the S‐(+)‐MHD enantiomer compared to R‐(−)‐MHD and an AUC0‐12S‐(+)/R‐(−) ratio of 5.44. Chirality 25:897–903, 2013. © 2013 Wiley Periodicals, Inc.